Career guidance decision support system (CareGuiDeSS) - Abdul Hamid, Mohd Noor; Mohmad Kamal, Fazillah; Wook, Muslihah (2007)
This study focuses on developing Internet-based career guidance Decision Support System for Decision Sciences students in Universiti Utara Malaysia. Admittedly that information on Decision Sciences field is relatively new in Malaysia and in lieu of that reason and plus the enthusiastic acceptance among participating candidates in several works provides a reason to be optimistic about the future use of the format.The Analytical Hierarchy Process (AHP) technique has been adopted in the design of the system to suggest the best potential job sector that suits the end user.Furthermore, the system takes into consideration all major factors that influence career choice and make it a reliable source for career guidance.In effort to provide such information, questionnaires have been distributed to all Decision Sciences graduates enquiring the details of their current job and the information obtained were used in the development of the system database.As a conclusion, the finding of this study is expectantly may assist Decision Sciences students in planning their future career.